2001
DOI: 10.1080/105504901750160484
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risks and Benefits of Benzodiazepines for Anxiety Disorders in Patients with a History of Substance Abuse or Dependence

Abstract: In this article, the authors reevaluate the traditional position that benzodiazepines should be avoided in anxiety disorder patients with a history of substance abuse or dependence. The efficacy of benzodiazepines in each of the anxiety disorders is reviewed, as are their side effects and toxicity. The definitions of benzodiazepine abuse and dependence are discussed, and relevant animal, experimental, and clinical data are reviewed and analyzed. A manual and computerized (MEDLINE) search was performed from 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 175 publications
(151 reference statements)
0
11
0
Order By: Relevance
“…It has been suggested that the empirical evidence regarding these concerns is lacking, and benzodiazepines may be safely used to treat anxiety disorders in some patients with a SUD (Posternak & Mueller, 2001), but this approach remains controversial. Buspirone, an anxiolytic with low abuse potential, has been shown to be efficacious in some studies in individuals with alcohol use problems and who are anxious (Kranzler et al, 1994; Malec, Malec, Gagne, & Dongier, 1996; McKeehan & Martin, 2002), but the results are mixed (Malcolm et al, 1992; Tollefson, Montague-Clouse, & Tollefson, 1992), and more evidence is needed.…”
Section: Generalized Anxiety Disordermentioning
confidence: 99%
“…It has been suggested that the empirical evidence regarding these concerns is lacking, and benzodiazepines may be safely used to treat anxiety disorders in some patients with a SUD (Posternak & Mueller, 2001), but this approach remains controversial. Buspirone, an anxiolytic with low abuse potential, has been shown to be efficacious in some studies in individuals with alcohol use problems and who are anxious (Kranzler et al, 1994; Malec, Malec, Gagne, & Dongier, 1996; McKeehan & Martin, 2002), but the results are mixed (Malcolm et al, 1992; Tollefson, Montague-Clouse, & Tollefson, 1992), and more evidence is needed.…”
Section: Generalized Anxiety Disordermentioning
confidence: 99%
“…Benzodiazepines were recently explored (in combination with disulfiram) for the treatment of AUD in individuals with co-occurring anxiety in a 16-week open-label trial, at the end of which the benzodiazepine was tapered off (clinicaltrials.gov identifier: NCT00721526; manuscript under preparation). Benzodiazepines are commonly used to lower anxiety levels during treatment of alcohol withdrawal, and they may decrease craving, but there are few studies of their longterm effects on alcohol consumption (Mayo-Smith, 1997; Posternak & Mueller, 2001). The rationales for combining a benzodiazepine with disulfiram in this clinical trial were that the benzodiazepine could serve as a positive reinforcer for taking the disulfiram, and could decrease anxiety and insomnia symptoms (possible relapse triggers) (Brower, 2003; Posternak & Mueller, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Benzodiazepines are commonly used to lower anxiety levels during treatment of alcohol withdrawal, and they may decrease craving, but there are few studies of their longterm effects on alcohol consumption (Mayo-Smith, 1997; Posternak & Mueller, 2001). The rationales for combining a benzodiazepine with disulfiram in this clinical trial were that the benzodiazepine could serve as a positive reinforcer for taking the disulfiram, and could decrease anxiety and insomnia symptoms (possible relapse triggers) (Brower, 2003; Posternak & Mueller, 2001). Moreover, in addition to preventing drinking via its usual mechanism (expectation of the alcohol-disulfiram reaction), disulfiram could minimize one of the primary risks of benzodiazepines (sedation in combination with other sedating drugs) by discouraging concurrent heavy drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Although persons with opioid use disorders use BZDs for intended anxiolytic reasons (Fatseas, Lavie, Denis, & Auriacombe, 2009) and as a sleep aid (Gelkopf, Bleich, Hayward, Bodner, & Adelson, 1999; Posternak & Mueller, 2001; Vogel et al, 2013), BZDs are commonly used in conjunction with opioids to enhance their rewarding effects or “high” (Chen et al, 2011; Fatseas et al, 2009; for review see Jones, Mogali, & Comer, 2012) or to decrease the effects of opiate withdrawal (Stein et al, 2016). Not surprisingly, BZD use among opioid dependent persons is associated with heightened risk.…”
Section: 0 Introductionmentioning
confidence: 99%